PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MIE INSTAN MEREK MIE SEDAAP SERTA IMPLIKASINYA TERHADAP LOYALITAS PELANGGAN DI PERUMAHAN PEKAYON BEKASI SELATAN - Cicih Ratnasih; Siti Nurjanah (Jurnal Manajemen FE-UB, 2019)
This study aims to examine and analyze the effect of Price and Product Quality on theDecision of Purchasing Instant Noodle Brand with Sedaap Noodles and Their Implications onCustomer Loyalitas` in Pekayon Jaya Bekasi South Housing.The data used in this study are primary data taken from the responses of questionnaires bythe community in Pekayon Jaya South Bekasi housing. The data processing method uses the pathanalysis method with the help of the SPSS analysis tool version 22. Statistical testing in this studyuses a model suitability test (goodness) of fit test).The results showed that the price effect had a positive and significant effect directly orindirectly through purchasing decisions on Customer Loyalty, Product quality had a positive andsignificant effect directly or indirectly through purchasing decisions on customer loyalty andpurchasing decisions had a direct positive effect on Loyalty Customer.Keywords: Price Effect, Product Quality, Purchasing Decisions, Customer Loyalty.